The Former Yugoslav Republic of Macedonia Student Assessment : SABER Country Report 2012 - World Bank Group (World Bank, Washington, DC, 2016)
In 2001, FYR Macedonia embarked on a new education policy agenda. One of the goals of this agenda was to improve the country’s student assessment system. In order to gain a better understanding of the strengths and weaknesses of its existing assessment system, FYR Macedonia decided to benchmark this system using standardized tools developed under The World Bank’s Systems Approach for Better Education Results (SABER) program. SABER is an evidence-based program to help countries systematically examine and strengthen the performance of different aspects of their education systems. The key policy areas for this student assessment status are as follows: (i) Classroom Assessment; (ii) Examinations; (iii) National Large-Scale Assessment (NLSA); and (iv) International Large-Scale Assessment (ILSA).